Nursing professionals’ knowledge about erythropoietin - Barbosa, Islene Victor; Maia, Sayonnara Ferreira; Melo, Elizabeth Mesquita; Studart, Rita Mônica Borges; Lima, Francisca Elisângela Teixeira; Carvalho, Zuíla Maria de Figueiredo (Revista da Escola de Enfermagem da USP, 2011)
This study was performed with the objective to evaluate the knowledge that nursing professionals have about the process of preserving, preparing and administering erythropoietin (EPO). This exploratory, descriptive study used a quantitative approach. It was performed at a Dialysis Center, from January to March 2009, and consisted on applying a questionnaire to 40 nursing professionals. All ethical aspects were taken into consideration. About the interaction of EPO with the patients' blood pressure, 87.5% had inadequate knowledge; only 32% knew the ideal temperature to preserve the drug, and 52.5% believe that it should be removed from the refrigerator about 15 to 30 minutes before its administration; intravenous administration was the most reported. Among the care before the administration, the most frequent was checking the expiration date; 57.5% used exclusive syringe for the administration and 95% usually register having administered the drug.